2017
DOI: 10.5334/joh.2
|View full text |Cite
|
Sign up to set email alerts
|

Arduino-Like Development Kit for Single-Element Ultrasound Imaging

Abstract: An open-source software ecosystem for ultrasound imaging is widely available to developers, however, limited resources can be found on the open-hardware side. The focus of this work was to develop an easy-to-use platform kit (hardware and software) for providing the community a complete experimental setup for ultrasound imaging at a low cost, without the need for expensive and non-modifiable specific equipment. The goal of this work resembles the needs of medical systems in the 80's where analog techniques usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Secondly, even when people publish work describing a hacked, recreated ultrasound machine, the individual components can be too expensive for a university laboratory to mass purchase. The audience of such expensive and complex homemade ultrasound scanner is usually the technology-enthusiasts or electronic specialists rather than university students [5].…”
Section: Pedagogical Needmentioning
confidence: 99%
“…Secondly, even when people publish work describing a hacked, recreated ultrasound machine, the individual components can be too expensive for a university laboratory to mass purchase. The audience of such expensive and complex homemade ultrasound scanner is usually the technology-enthusiasts or electronic specialists rather than university students [5].…”
Section: Pedagogical Needmentioning
confidence: 99%
“…[47] are not very conclusive. In this direction, a significant improvement over [47] is Jonveaux [53]. Jonveaux has described a highly modular ultrasound imaging platform based on microcontrollers and not using FPGAs altogether.…”
Section: Open Electronics In Medical Ultrasound Imagingmentioning
confidence: 99%
“…Jonveaux has described a highly modular ultrasound imaging platform based on microcontrollers and not using FPGAs altogether. Hence it might be very promising to combine the work of Jonveaux [53] with annular array transducers for high-resolution imaging. Further, the work of Jonveaux [53] provides a very comprehensive reference for researchers interested in low-cost microcontroller-based systems and avoiding the complexities associated with using FPGAs.…”
Section: Open Electronics In Medical Ultrasound Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In MedTech too a range of open source hardware projects can be found that aim to provide low-cost, adaptable and patient-specific alternatives to proprietary products for private use, e.g. myoelectric prostheses (e-Nable, MyOpen), CT scanners (Tricorder project), echo-stethoscopes (echOpen (Jonveaux, 2017)), infusion pumps (OpenPump), physiological monitoring systems (open-BCI), diabetes treatment (Diabeto, openAPS) (Niezen, Eslambolchilar and Thimbleby, 2016;Moritz, Redlich, and Wulfsberg, 2018). For commercialization of these products, however, approval of authorities of the corresponding markets would be required regarding the safe use of a product.…”
Section: Introductionmentioning
confidence: 99%